Finite element modeling, analysis and fatigue life prediction of lower suspension arm - M. M., Rahman; M.M., Noor; K., Kadirgama; Rosli, A. Bakar; M. R. M., Rejab (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.